2015
DOI: 10.1111/aas.12527
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone added to bupivacaine or bupivacaine–fentanyl prolongs motor and sensory block during supraclavicular brachial plexus blockade: a randomized clinical trial

Abstract: Addition of naloxone to bupivacaine in supraclavicular brachial plexus block prolonged the duration of the neural blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…In association with a recent study, adding a low dose of naloxone (100 ng) to 30 mL of 0.5% bupivacaine (150 mg) prolonged the duration of nerve block during the supraclavicular brachial plexus block . The sensory block duration in patients received 30 mL bupivacaine with 100 ng naloxone was almost 1.6‐folds longer than that in patients received 30 mL bupivacaine alone . This dose of naloxone is less than 0.1% of that used in the present study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In association with a recent study, adding a low dose of naloxone (100 ng) to 30 mL of 0.5% bupivacaine (150 mg) prolonged the duration of nerve block during the supraclavicular brachial plexus block . The sensory block duration in patients received 30 mL bupivacaine with 100 ng naloxone was almost 1.6‐folds longer than that in patients received 30 mL bupivacaine alone . This dose of naloxone is less than 0.1% of that used in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, we showed that combined injection of the subthreshold‐dose naloxone with lidocaine displays a supra‐additive analgesic effect. In association with a recent study, adding a low dose of naloxone (100 ng) to 30 mL of 0.5% bupivacaine (150 mg) prolonged the duration of nerve block during the supraclavicular brachial plexus block . The sensory block duration in patients received 30 mL bupivacaine with 100 ng naloxone was almost 1.6‐folds longer than that in patients received 30 mL bupivacaine alone .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Naloxone, which gains its popularity as an opioid antagonist, might induce an analgesic effect. Few studies have been published on the use of naloxone for pain relief when added in low dose with LAs in various nerve blockades [5,6,11]. Naloxone produces a dose-dependent pain response; in the rat model, small doses of naloxone produced paradoxical analgesia, while larger doses resulted in hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone, which is known as an opioid antagonist, used to counter the effects of opioid overdose, has been used in low dose as an additive to LA drugs to prolong sensory and motor nerve blocks in supraclavicular brachial plexus blockade and peribulbar anesthesia [5,6].…”
Section: Introductionmentioning
confidence: 99%